2017
DOI: 10.1016/j.ijrobp.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Qualitative and Quantitative Analysis of Real-Time Peer Review Quality Assurance Rounds Incorporating Direct Physical Examination for Head and Neck Cancer Radiation Therapy

Abstract: Purpose and Objectives Our department has a long-established comprehensive quality assurance (QA) planning clinic for patients undergoing radiation therapy (RT) for head and neck cancer. Our aim is to assess the impact of a real-time peer review QA process on the quantitative and qualitative radiation therapy plan changes in the era of intensity modulated RT (IMRT). Methods and Materials Prospective data for 85 patients undergoing head and neck IMRT who presented at a biweekly QA clinic after simulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 16 publications
(27 reference statements)
0
42
3
Order By: Relevance
“…Lastly, while head and neck cancers are most common on male patients, we found that approximately 90% of cases in this dataset were male. This proportion of male patients is slightly higher than our previous report of approximately 75% of patients treated at our clinic for head and neck cancers.…”
Section: Discussioncontrasting
confidence: 69%
“…Lastly, while head and neck cancers are most common on male patients, we found that approximately 90% of cases in this dataset were male. This proportion of male patients is slightly higher than our previous report of approximately 75% of patients treated at our clinic for head and neck cancers.…”
Section: Discussioncontrasting
confidence: 69%
“…All plans were 9 beam step-and-shoot intensity modulated radiation therapy plans in adherence to the RTOG treatment guidelines. They were peerreviewed [8][9][10]. For daily position verification, the patient was aligned to treatment position using skin marks on the linear accelerator, then the table turned 180 degrees and CToR scan was made in treatment position.…”
Section: Methodsmentioning
confidence: 99%
“…TV definition was done in the Pinnacle treatment planning system (Pinnacle, Phillips Medical Systems, Andover, MA), with rigorous multi-physician quality assurance. [18]…”
Section: Methodsmentioning
confidence: 99%